Waitresses in Action: Feminist Labour Protest in 1970s Ontario - Sangster, Joan (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
In the 1970s, women in Toronto created the Waitresses Action Committee to protest the introduction of a “differential” or lower minimum wage for wait staff serving alcohol. Their campaign was part of their broader feminist critique of women’s exploitation and the gendered and sexualized nature of waitressing. Influenced by their origins in the Wages for Housework campaign, they stressed the linkages between women’s unpaid work in the home and the workplace. Their campaign eschewed worksite organizing for an occupational mobilization outside of the established unions; they used petitions, publicity, and alliances with sympathizers to try to stop the rollback in their wages. They were successful in mobilizing support but not in altering the government’s decision. Nonetheless, their spirited campaign publicized new feminist perspectives on women’s gendered and sexualized labour, and it contributed to the ongoing labour feminist project of enhancing working-class women’s equality, dignity, and economic autonomy. An analysis of their mobilization also helps to enrich and complicate our understanding of labour and socialist feminism in this period.